Coopetitive Games for Sustainability of Global Feeding and Climate Change: Recent Developments - CARFÌ, David; DONATO, Alessia (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018, 2018)
In this paper, we face the problem of global feeding sustainability and related environmental issues, with a strong attention to possible public heath improvements. In particular, we consider food producers and sellers of vegan (or vegetarian) and non-vegan (or non-vegetarian) food and we build up feasible and measurable contracts between two different food producers, in order to construct a more sustainable and healthier diet for future generations. At this aim, we use co-opetitive approach by means of game theory. Our co-opetitive approach consists in a game theory structure, which could help small local producers of vegan food a simpler entry in the global market and free significant publicity. At the same time, our mathematical construction suggests how big global producers/sellers of non-vegetarian food could develop a smooth rapid transaction to a more sustainable and healthier production/supply. Specifically, our game constitutes an asymmetric R&D alliance between McDonald’s and the local producer of the so called vegan product "Muscle of Wheat". We finally show a quantitative compromise solution, obtained by the Kalai-Smorodinsky principles, in a numerical study (exemplary) case.